Multifunctional Cyclopentadienes as a Scaffold for Combinatorial Bioorganometallics in [(η5‐C5H2R1R2R3)M(CO)3] (M=Re, 99mTc) Piano‐Stool Complexes. Issue 40 (21st June 2018) - Frei, Angelo; Spingler, Bernhard; Alberto, Roger
Abstract: Multifunctional cyclopentadiene (Cp) ligands and their rhenium and 99m Tc complexes were prepared by a versatile synthetic route. The properties of these Cp ligands can be tuned on demand, either during their synthesis (variation of R1 ) or through post‐synthetic functionalization with two equal or different vectors (V1 and V2 ). Variation of these groups enables a combinatorial approach in the synthesis of bioorganometallic complexes. This is demonstrated by the preparation of Cp ligands containing both electron‐donating and electron‐withdrawing groups at the R1 position and their subsequent homo‐ or heterofunctionalization with biovector models (benzylamine and phenylalanine) under standard amide bond‐formation conditions. All ligands can be coordinated to the fac ‐[Re(CO)3 ] + and fac ‐[ 99m Tc(CO)3 ] + cores to give tetrafunctional complexes in straightforward and functional‐group‐tolerant procedures. The 99m Tc complexes were prepared in one step, in 30 min, and under aqueous conditions from generator‐eluted [ 99m TcO4 ] − . Abstract : Multiply substituted Cp ligands : Multifunctional cyclopentadiene ligands with tuneable properties and their rhenium and 99m Tc complexes were prepared by a versatile synthetic route. The properties of these Cp ligands can be tuned on demand, either during their synthesis (variation of R1 ) or through post‐synthetic functionalization with two equal or different vectors (V1 and V2 ; see scheme). Variation of these groups enables a combinatorial approach in the synthesis of bioorganometallic complexes.